Corrigendum: Changes to the Author List and Acknowledgements - Muhsan Ali Kalhoro; Veeranjaneyulu Chinta; Muhammad Tahir; Yujie Sheng; Chunli Liu; Zhiyuan He; Zhenlin Liang; Jun Song; Tony Song (Algae, 2026)

Spatiotemporal variations of phytoplankton functional groups and environmental drivers over the past two decades in the Bohai, Yellow and East China Sea - Muhsan Ali Kalhoro; Veeranjaneyulu Chinta; Muhammad Tahir; Yujie Sheng; Chunli Liu; Zhiyuan He; Zhenlin Liang; Jun Song; Tony Song (Algae, 2025)
Phytoplankton, the primary producers of marine ecosystems, play a crucial role in sustaining primary production. This study investigates spatiotemporal variations in phytoplankton functional groups (PFGs) and their environmental drivers across the Bohai, Yellow, and East China Seas (BYECS) from 2003 to 2022. Sea surface temperature exhibited a significant warming trend (sea surface temperature [SST]; τ > 0.48, p